Monuments of Oirat Buddhist architecture in Kazakhstan: problems of studying the historical and cultural heritage of the Kalmyks in the works of prof. Zh. O. Artykbayev - S. Chuluun; E. Omakaeva (Nomadic Civilization: Historical Research, 2021)
The article analyzes the views of the famous Kazakh historian Zh.O. Artykbaev on the problems of preserving and studying the historical and cultural heritage of the Kalmyks. In the works of the scientist, special attention is paid to archaeological monuments, Buddhist monasteries, memorial sites, cultural and natural landscapes associated with the ethnic history of the Kalmyks and Oirats, military events, and the life of prominent historical ﬁgures. The task is to develop systematically an integral concept for the preservation, actualization and scientiﬁc study of historical and cultural heritage as a new interdisciplinary ﬁeld of knowledge at the intercountry, all-Russian, regional and local levels, taking into account the accumulated domestic and foreign experience, the optimal model of informatization of heritage, the use of environmental monitoring tools to modern the state of objects of historical and cultural heritage and unique territories. The national historical and cultural heritage of the Kalmyk people is the code of its self-identiﬁcation. The essence of national self-identiﬁcation is seen in the unity of inheritance and actualization of cultural knowledge and values accumulated by past generations. Today, more than ever, it is important to understand and realize the need to preserve knowledge about their cultural and historical past. The historical and cultural heritage of the nomadic civilizations of Central Asia, which includes a vast complex of old-written monuments, places of worship, archaeological artifacts and other various items of material culture, has a huge information potential and allows you to get to know the spiritual culture of nomads more deeply.